Innovation through recycling in Iron Age plaster technology at Tell el-Burak, Lebanon - Amicone, Silvia; Orsingher, Adriano; Cantisani, Emma; Calandra, Sara; Badreshany, Kamal; Spiteri, Cynthianne; Berthold, Christoph; Sader, Hélène; Schmitt, Aaron; Kamlah, Jens (Scientific reports, 2025)
Recent excavations at the Phoenician coastal site of Tell el-Burak, a large-scale agricultural production centre in use during 725-350 BCE, have uncovered the first Iron Age wine press in Lebanon. This discovery enabled a systematic, interdisciplinary study of its plaster, offering insights into ancient construction technologies. The analysis extended to two other plastered installations found in separate rooms within the complex, allowing for a comprehensive comparison. An integrated program of archaeometric analysis, including optical microscopy in polarising light, X-ray powder diffraction, scanning electron microscopy, thermogravimetry, and organic residue analysis, was applied to samples from these three structures to investigate plaster composition and technological variability. Previous studies identified the use of crushed ceramic fragments in a lime-based plaster. Now, new analyses provide deeper insights into the nature of the binder, revealing how the addition of ceramic sherds may have enhanced the plaster’s mechanical properties and hydraulicity, making it a significant early example of hydraulic mortar. These findings confirm the existence of a local, innovative tradition of lime-plaster manufacture in southern Phoenicia. This investigation not only sheds light on the specific technological practices of Tell el-Burak, but also contributes to the broader understanding of Phoenician and Punic technological advancements in the Iron Age Mediterranean.
Veröffentlicht: 07. Juli 2025
Gesehen am 21.01.2026